Human–nature connectedness and sustainability across lifetimes: A comparative cross‐sectional study in France and Colombia - Gladys Barragan‐Jason; Maxime Cauchoix; Paula A. Diaz‐Valencia; Arielle Syssau‐Vaccarella; Solène Hemet; Camilo Cardozo; Suzanne M. Skevington; Philipp Heeb; Camille Parmesan (People and Nature)
Abstract To achieve sustainable targets, international panels call for a transformative change in human–nature interactions to foster human well‐being and promote pro‐environmental behaviour. The extent to which people considered themselves as part of nature—known as human–nature connectedness—has been shown to be a key societal trait for achieving such a transformative change. Human–nature connectedness is linked to improved human welfare and actions for nature conservation and can be increased by direct contact with natural environments in adults living in the Global North. It has not been shown whether these relations are true across lifetimes and in the Global South, making it difficult to generalise about the effects of human–nature connectedness globally. Here, we conducted a cross‐sectional study to examine and compare human–nature connectedness across ages in 1858 participants aged 3–87 years from two countries: France (N = 1059) and Colombia (N = 799). We also investigated the links between human–nature connectedness, pro‐environmental behaviours, well‐being and two indicators of opportunity to experience nature (i.e. degree of urbanisation and forest cover around the participants' municipality of residence). Results show that human–nature connectedness is positively related to well‐being and pro‐environmental behaviours in both countries. Analyses revealed an age‐related pattern of human–nature connectedness with a significant decline from childhood to the mid‐teens in both countries. Overall, Colombian participants have a higher human–nature connectedness than French participants and individuals' human–nature connectedness was negatively linked to the urbanisation's indices in both countries. Here, we show that human–nature connectedness is linked to sustainable outcomes in a Global South country, just as it is in the Global North. Our study also suggests that increasing contact with nature during formative teenage years could mitigate the observed decline in human–nature connectedness. Future studies are warranted combining qualitative and quantitative measures related to human–nature connectedness, nature experiences, values and practices in relation to nature, in multiple countries from the global South. Our study indicates that enhancing human–nature connectedness could provide an additional tool for achieving sustainable targets globally, not just in highly developed northern‐hemisphere countries. Read the free Plain Language Summary for this article on the Journal blog.